2013
DOI: 10.1080/13676261.2013.830704
|View full text |Cite
|
Sign up to set email alerts
|

Social differentiation in young people's political participation: the impact of social and educational factors on youth political engagement in Britain

Abstract: Over the course of the last decade, policy makers in Britain have become increasingly concerned about the apparent and persisting withdrawal by young people from the formal political process. In this article, the authors consider the results from a representative online national survey of 1025 British 18-year-olds conducted in 2011, including both those who voted at the 2010 General Election and those who did not. The findings reveal that young people do profess a commitment to the political process, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 45 publications
14
128
0
7
Order By: Relevance
“…They are also disappointed with policies offered by political parties, suggesting that there is little to separate the policy direction of political parties [10] and that such policies are not relevant to young people [27]. Contemporary youth are also disinclined to involve themselves in political party structures as they feel they are hierarchical and centralised, offering little opportunity for them to influence the creation of policy exchange information with political representatives [8,11]. Consequently, there is substantial evidence that young people are now replacing participation in formal politics with engagement with alternative (often more individualistic) forms of political action (boycotting, attending demonstrations, signing petitions) [11,38,39].…”
Section: Young People's Withdrawal From Formal Politicsmentioning
confidence: 99%
See 4 more Smart Citations
“…They are also disappointed with policies offered by political parties, suggesting that there is little to separate the policy direction of political parties [10] and that such policies are not relevant to young people [27]. Contemporary youth are also disinclined to involve themselves in political party structures as they feel they are hierarchical and centralised, offering little opportunity for them to influence the creation of policy exchange information with political representatives [8,11]. Consequently, there is substantial evidence that young people are now replacing participation in formal politics with engagement with alternative (often more individualistic) forms of political action (boycotting, attending demonstrations, signing petitions) [11,38,39].…”
Section: Young People's Withdrawal From Formal Politicsmentioning
confidence: 99%
“…While conventional wisdom suggests this reluctance to participate may be due to young people's indifference towards politics, a number of scholars, associated with the anti-apathy school [7], have suggested that the relationship between contemporary youth and formal politics is far more complex. Their studies indicate that far from being apathetic, young people are interested in politics and support democracy [8], but don't trust the motives of politicians [9] and are unhappy with political parties for being remote, hierarchical and centralised [10]. Closely aligned to the anti-apathy thesis is the notion that young people are rejecting formal politics and are channelling their political activities into alternative forms of political engagement [11].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations